Effect of Mobile Health Technology on Weight Control in Adolescents and Preteens: A Systematic Review and Meta-Analysis - Yien, Jui-Mei; Wang, Hsiu-Hung; Wang, Ruey-Hsia; Chou, Fan-Hao; Chen, Kuo-Hsiung; Tsai, Fu-Sheng (Frontiers in Public Health, 2021)
Childhood obesity is a crucial public health concern. In recent years, numerous studies have employed mobile health technology applications for weight control in children but obtaining varying effects. We conducted a meta-analysis to discuss the effectiveness of mobile health technology in reducing the body mass index (BMI) of obese children. The standardized mean difference (SMD) in BMI between the intervention and control groups was employed to measure the effect of mobile health technology intervention on weight control. The Comprehensive Meta-Analysis Version 3 software was employed for meta-analysis, and the results are presented in a forest plot. This study included nine randomized control trials, which featured a total of 1,202 participants. The meta-analysis revealed that mobile health technology intervention did not have a significant weight loss effect on subjects with obesity. However, by using ethnicity as a moderating variable for subgroup analysis, we discovered that the BMI of ethnic Chinese groups who received mobile health technology intervention was significantly lower than that of the control group. This effect was not significant in the nonethnic Chinese subgroup. Therefore, the use of mobile health technology intervention for weight control in ethnic Chinese children resulted in significantly lower BMI in these children; however, the use of mobile health technology intervention for weight control is unsuitable for nonethnic Chinese children.